Electroconvulsive Therapy for Intractable Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Two children aged 13 and 10 years with intractable epilepsy were treated with electroconvulsive therapy (ECT) for seizure control at the Children's Hospital, Charleston, SC.